Food allergy diagnosis in patients with elimination diet history. Preliminary report - Elsy Maureen Navarrete-Rodríguez; Blanca Estela Del Río-Navarro; César Fireth Pozo-Beltrán; Daniela Edith García-Fajardo; Omar Josué Saucedo-Ramírez; Enrique Emanuel Castelán-Chávez (Revista Alergia México, 2014)
Background: Food allergy diagnosis is performed by a double blind placebo controlled challenge; however, in a lot of patients, it is only based on clinical history, skin prick tests, or parents’ perception. There is a high frequency of elimination diets without an adequate approach.